Islamic Parenting dalam Mendidik Anak di Era Modern Menurut Perspektif Islam - Robiansyah, Firman; Zahra, Fadma Alyah; Lutfiiah, Ratu Siti; Zailanty, Shofia (Jurnal Wanita dan Keluarga, 2024)
The ideal family according to Islam is described in the Qur'an as a family that practices Islamic law with full awareness and obedience. This includes fearing Allah, creating a family that lives in balance with the teachings of Islam, and maintaining values and faithfulness in family life. Islam emphasizes the importance of the family as the main foundation in the formation of a good society. Interpretations of the Qur'an by Sayyid Outb and the Indonesian Ministry of Religious Affairs highlight the need to protect the family from the threat of hell. In Indonesia, there are several ideal family types, including nuclear, conjugal and extended families, each with defined roles for the father, mother and children. Roles in the ideal family include breadwinning, education, protection, as well as the development of children's psychosocial aspects according to their development. This research compares theories, findings and analysis to answer the problem statement clearly and concisely.